Differences in therapeutic effects of topically applied corticosteroid and tacrolimus on atopic dermatitis-like symptoms in NC/Nga mice. Issue 1 (April 2017) - Noguchi, Atsushi; Tominaga, Mitsutoshi; Takahashi, Nobuaki; Matsuda, Hironori; Kamata, Yayoi; Umehara, Yoshie; Ko, Kyi Chan; Suga, Yasushi; Ogawa, Hideoki; Takamori, Kenji
Highlights: TAC, not BMV, reduced scratching and improved dermatitis in Dfb-NC/Nga mice. Strongest steroid CBP reduced scratching and improved dermatitis in Dfb-NC/Nga mice. The therapeutic efficacies of CBP and TAC on AD-like symptoms were similar. Early antipruritic effects of TAC and CBP are unrelated to epidermal innervation. Abstract: Background: Topical corticosteroid and calcineurin inhibitor have similar therapeutic benefits in atopic dermatitis (AD), but the differences in therapeutic mechanisms of action of these agents against AD symptoms are not fully understood. Objective: This study was performed to examine the different effects of topical betamethasone valerate (BMV), clobetasol propionate (CBP), and tacrolimus (TAC) on itch-related behavior and dermatitis in NC/Nga mice with AD-like symptoms. Methods: AD-like dermatitis was induced in the dorsal skin of NC/Nga mice by repeated topical application of Dermatophagoides farinae body (Dfb) ointment twice weekly for three weeks. Mice with dermatitis scores over 5 were divided into five groups with equal dermatitis scores and treated with BMV, CBP, TAC, or Vaseline (Vas) once daily for two consecutive days, or were not treated (NT). Scratching behavior was analyzed using a SCLABA ® -Real system. Transepidermal water loss (TEWL) before and after treatment was measured using a Tewameter ® TM210. Skin collected from each group was analyzed histologically. Results: After the second treatment, dermatitis showed significantly greater improvement in the CBP and TAC-treated groups than in the Vas-treated and NT groups. The numbers of scratching bouts were significantly lower in CBP and TAC-treated mice than in Vas-treated mice. TEWL was significantly lower in TAC-, but not in CBP-, treated mice than in Vas-treated mice. Immunohistochemical examination showed that BMV, CBP and TAC did not reduce the increased densities of epidermal protein gene product 9.5- and substance P-immunoreactive fibers. The numbers of dermal CD4-immunoreactive T cells were significantly lower in BMV and CBP-treated mice than in Vas-treated and NT mice. The numbers of dermal eosinophils were significantly lower in BMV, CBP and TAC-treated mice than in Vas-treated and NT mice, with CBP showing the strongest effect. CBP significantly reduced epidermal thickness compared with Vas and NT. There were no significant differences in the numbers of interleukin-31-immunoreactive cells and mast cells, or in expression of epidermal thymic stromal lymphopoietin among all five groups. Conclusion: The therapeutic potency of TAC against AD-like symptoms, including pruritus, is equal to that of the corticosteroid CBP. Epidermal innervation of sensory nerves itself might not be related to the therapeutic effects of topical tacrolimus and corticosteroids in its early phase.